The Influence of Student Self-Efficacy at School on the Quality of Religious Education Teachers as Murabbi - Muhdi, Ali; Suwito, Suwito; Afandi, Rahman; Purnama, Yulian; Azis, Abd. (Mimbar Sekolah Dasar, 2024)
The importance of the role of teachers as agents of change and understanding the relationship between the level of student independence and the quality of religious teachers in schools. However, in fact, there are differences between expectations and reality on the ground, religious education has decreased among students. So, it is necessary to carry out research with the aim of finding out the relationship between the level of student independence and the quality of Islamic education teachers (IET) as murabbi. This research method uses a quantitative approach with a questionnaire as the main research instrument. Respondents consisted of 554 IET primary and secondary school teachers in Indonesia, who were selected using a multistage cluster sampling technique. Data collection techniques were through structured questionnaires which were analyzed using SPSS Version 25.0. The data analysis technique uses SPSS Version 25.0 to gain meaningful insight from the IET response. As a result, it was found that there was a positive correlation between the level of student independence and the quality of IET Islamic education teachers as murabbi. In conclusion, it is important to pay attention to the level of student independence in improving the quality of religious teacher teaching. The research implications have an impact on the development of religious education in primary and secondary schools.